Capturing design rationale - Bracewell, Rob; Wallace, Ken; Moss, Michael; Knott, David (Computer aided design, 2009)
The subject of this paper is the Design Rationale editor (DRed). This is a simple and unobtrusive software tool that allows engineering designers to record their rationale as the design proceeds. DRed is one of the latest of many derivatives of the venerable IBIS concept. Thus it allows the issues addressed, options considered, plus associated pro and con arguments, to be captured in the form of a directed graph of dependencies. The research was conducted in close collaboration with, deployed, and tested in a major multinational aerospace company. The paper describes the main features of the tool, by means of a real design example from the company. It then examines the methodology and process by which the tool was researched, implemented and introduced into industrial practice. Finally, DRed is compared with other IBIS-based software, to identify and explain how it addresses problems that seem to have made earlier tools unsuitable for routine use by designers. Simplicity seems to be a key factor for real world acceptance of such tools.